Criminal Act Of Travel Document Fraud Reviewed Based On Law Number 6 Year 2011 On Immigration - Azis, Teuku Putra; Hatta, Muhammad; Jumadiah, Jumadiah (International Journal of Law, Environment, and Natural Resources, 2022)
The crime of document fraud committed by Malaysian foreign nationals is charged with Article 126 letter c and Article 127 of Law Number 6 of 2011 concerning Immigration. The form of immigration crime committed was passport forgery so that the perpetrator was sentenced to 1 year in prison and a fine of IDR 1.000.000. However, the sentence is considered too low so that it does not provide a deterrent effect to the perpetrators of immigration crimes. Supposedly, the judge can decide on a heavier sentence based on the provisions in Article 126 letter c and Article 127 of Law Number 6 of 2011 concerning Immigration.